Application of progressive muscle relaxation therapy to reduce anxiety in clients with hypertension: A case study - Lailatul Fitria; Erti Ikhtiarini Dewi; Fitrio Deviantony; Amalia Kusumaningsih (School of Health Sciences Al-Ma'arif, 2025)
Background: Hypertension is frequently associated with psychological disorders, particularly anxiety, which may worsen physiological responses and lead to decreased quality of life. Progressive Muscle Relaxation (PMR) is a non-pharmacological intervention proven to reduce anxiety and enhance psychological and physiological stability among clients with chronic diseases. Objective: This case study aimed to evaluate the effectiveness of PMR therapy in reducing anxiety levels in a hypertensive client. Methods: A single-case study design using a nursing care approach was implemented on a client diagnosed with stage 2 hypertension and moderate anxiety based on the Hamilton Anxiety Rating Scale (HARS). PMR therapy was performed once daily for five consecutive days, supported by assessments through interviews, observation, vital sign monitoring, and HARS evaluation. Results: The client demonstrated a decrease in anxiety level from moderate (HARS score: 17) to mild (HARS score: 13) after five therapy sessions. Additional improvements were noted in sleep duration, perceived relaxation, and blood pressure stability. The client became able to independently perform PMR beginning on day three. Conclusion: Progressive Muscle Relaxation therapy demonstrated a positive impact on reducing anxiety among hypertensive clients when practiced consistently and systematically. PMR may be recommended as a complementary nursing intervention in community settings to improve psychological well-being and prevent hypertension-related complications. Further studies using larger sample sizes are recommended to strengthen generalizability.